ANALISIS SERAT OPTIK DENGAN MENGGUNAKAN METODE POWER BUDGET - Ayub Wimatra; Sunardi Sunardi (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2019)
In this optical fiber communication system the initial signal in the form of an electrical signal at the transmitter will be changed by the transducer into a light wave which is then transmitted through a fiber optic cable to the receiver located at the end of the cable. At the receiver the optical signal will be reproduced again by the transducer into an electrical signal. This study aims to analyze the performance due to the influence of optical fiber attenuation, connector damping attenuation resulting in a decrease in power in the optical fiber cable and analyze the results of calculations using the link power budget that aims to find the value of the Transsiver to the Receiver. The area or region observed is the Medan-Tebing Tinggi area with two measuring track areas namely the Range Range which has a range of 89.99 km and the Siantar line which has a range of 99.99 km. The method used is the measurement of power, measurement of attenuation and calculations using the link power budget. Comparison of the results of the two measuring devices used, the results of the two measuring devices do not differ greatly between the power meter with the OTDR. So it can be stated that to see the amount of attenuation, the results will be more accurate by using a power meter. Based on comparison of measurement results using oTDR with the results of calculations using the link power budget method it can be seen the level of performance of an optical fiber communication system. For Core 1 range, the comparison is 0.063% and 0.073% for core 2. while for Tebing Tinggi 1 core, the comparison result is 0.032% and 0.005% is obtained for core 2. it can be stated that the performance of the optical fiber communication system is normal and can be used to operate. So that when connecting the optical cable, if it is broken, it must be connected using the same cable and connecting the optical fiber when the core is sterile so that the connection is perfect.